How has process assessment been automated by organizations? A systematic literature mapping - Hauck, Jean Carlo Rossa; Galimberti, Maurício Floriano; Zwirtes, Augusto Guarda Lara; Bosse, Jacyara (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2021: Anais do XVII Simpósio Brasileiro de Sistemas de Informação, 2021)
Organizational process improvement initiatives typically apply some kind of process assessment. Even partial automation of these process assessments can be beneficial. In this sense, the aim of this study is to investigate the state of the art in automated process assessment. A systematic literature mapping is performed in order to answer the research question: What are the approaches to automated process assessment? Thus, the state of the art is analyzed following the steps of protocol definition, search execution, study selection and data extraction and synthesis. We found 16 studies that directly or indirectly use some kind of automated process assessment support. The approaches reported in these studies cover most of the steps expected in typical process assessments and used nine different software tools to support these steps. The main observed results of process assessment were reduction of effort, time and complexity and automated assessment feedback. There are two major contributions of this research: a comprehensive and structured overview of the state of the art in automated process assessment, contributing to the knowledge organization of this field; and an initial guide to organizations that want to apply efforts to automate their process assessments in choosing the tools, techniques and approaches, and knowing the expected outcomes of this kind of initiative.